CYTOTOXIC ACTIVITY OF ETHANOL EXTRACT Petrosia sp. IN VITRO AGAINST CANCER CELLS HeLa - Mentarry Bafadal; Wa Ode Mutiara; Muhammad Hajrul Malaka; Adryan Fristiohady; Agung W. M. Yodha; Baru Sadarun; Sahidin Sahidin (Universitas Muhammadiyah Magelang, 2021)
Cervical cancer is one of the highest causes of death in Indonesian women caused by mutations of normal cervical cells turning into abnormal cells. Treatment of cervical cancer causes significant side effects with a relatively long treatment period, so many researchers are exploring various natural ingredients from marine ecosystems as candidates for anticancer drugs. One of them is the sea sponge Petrosia sp. containing various secondary metabolites, one of which is an alkaloid that has a cytotoxic effect on cancer cell lines. This study aims to determine the cytotoxic activity of the ethanol extract of Petrosia sp. in HeLa cervical cancer cells. The ethanol extract of Petrosia sp. obtained by maceration using 96% ethanol and obtained extract as much as 55.9 g and yield value of 2.94%. Cytotoxic activity test was carried out in vitro using the Presto Blue method with varying concentrations of ethanol extract 7.81 ppm; 15.62 ppm; 31.25 ppm; 62.5 ppm; 125 ppm; 250 ppm; 500 ppm; and 1000 ppm. The cytotoxic parameter used was IC50 which was determined using the GraphPad Prism software version 5. The IC50 value of the marine sponge extract Petrosia sp. of 97.20 ppm or 97.20 g/ml with an active category as cervical anticancer. Cervical cancer is one of the highest causes of death in Indonesian women caused by mutations of normal cervical cells turning into abnormal cells. Treatment of cervical cancer causes significant side effects with a relatively long treatment period, so many researchers are exploring various natural ingredients from marine ecosystems as candidates for anticancer drugs. One of them is the sea sponge Petrosia sp. containing various secondary metabolites, one of which is an alkaloid that has a cytotoxic effect on cancer cell lines. This study aims to determine the cytotoxic activity of the ethanol extract of Petrosia sp. in HeLa cervical cancer cells. The ethanol extract of Petrosia sp. obtained by maceration using 96% ethanol and obtained extract as much as 55.9 g and yield value of 2.94%. Cytotoxic activity test was carried out in vitro using the Presto Blue method with varying concentrations of ethanol extract 7.81 ppm; 15.62 ppm; 31.25 ppm; 62.5 ppm; 125 ppm; 250 ppm; 500 ppm; and 1000 ppm. The cytotoxic parameter used was IC50 which was determined using the GraphPad Prism software version 5. The IC50 value of the marine sponge extract Petrosia sp. of 97.20 ppm or 97.20 g/ml with an active category as cervical anticancer.